Effect of Obesity on Hematological Parameters in Females from Babylon Province - Mohammed Ali Al-Jabory; Athmar Kadhim Gatea; Elaf Yousif Rashid Barem (Medical Journal of Babylon, 2025)
Background: Obesity is a prevalent and significant health issue worldwide. In Iraq, the prevalence of overweight/obesity stands at 66.9%. It is more prevalent among women than men. Obesity can affect any system in the body, including hematological parameters. The pro-inflammatory state associated with obesity is reflected in the higher white blood cell (WBC) count observed in most obese individuals compared to those with normal weight. While the link with anemia remains less certain, obesity is associated with both higher platelet count and activity. Objectives: We evaluate the differences in hematological parameters based on complete blood counts among normal, overweight, and obese females in Babylon Province. Materials and Methods: This cross-sectional study involved 365 females from Babylon Province. After obtaining consent, their height and weight were measured at a private clinic, with blood samples collected for complete blood count assessment using a five-differential auto-analyzer. Body mass index (BMI) was calculated by dividing the weight in kilograms by the square of the height in meters. Based on BMI, participants were categorized into three groups: normal, overweight, and obese. Results: Among the participants, 105 had a normal BMI with a mean age of 26.6 + 8.3 years and a mean BMI of 21.18 ± 1.25 kg/m2. Additionally, 125 were overweight with a mean age of 24.5 ± 5.3 years and a mean BMI of 23.8 ± 0.47 kg/m2. Furthermore, 135 were obese, with a mean age of 29 ± 5.3 years and a mean BMI of 29.85 ± 5.34 kg/m2. There were significant differences in WBC; P = 0.02) and absolute neutrophils count (ANC; P = 0.03) among the three groups, as well as in WBC (P = 0.01) and ANC (P = 0.01) between the obese and normal groups. Additionally, differences were observed in neutrophils/lymphocytes (N/L) ratio (P = 0.05) and platelet count (P = 0.04) between the overweight and normal groups. No significant differences were found in other parameters. Conclusion: Obesity exerts a significant impact on different body tissues, including the blood. Our study revealed that obesity is associated with a significant change in WBC, ANC, N/L ratio, and platelet count among different BMI groups of females in Babylon Province while showing no discernible effect on red blood cells and other platelet parameters.